Audit Energi Berbasis Hasil Pengukuran dan Monitoring Konsumsi Energi Listrik di Pollux Malls Paragon Kota Semarang - Dinara Alya Yuditha; Agus Adhi Nugroho (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Energy audits are an essential step in supporting the efficiency of electricity utilization, particularly in large-scale commercial buildings such as shopping malls. This study was conducted to measure and analyze electricity consumption at Pollux Malls Paragon Semarang using a direct measurement approach combined with historical monitoring of energy consumption. The main focus of the audit was on the lighting system and the Heating, Ventilation, and Air Conditioning (HVAC) system from the Basement to the 6th Floor. Measurement results showed that the Energy Consumption Intensity (ECI) ranged between 39.94–45.20 kWh/m²/month, far above the national efficiency standard (maximum 18.5 kWh/m²/month), indicating a highly wasteful energy usage condition. The two main systems contributing to the largest share of consumption were HVAC and lighting, with a combined estimated share exceeding 60% of the total monthly energy use. Based on the analysis, several energy-saving opportunities were identified, including the replacement of energy-efficient lighting (LED), installation of automatic control systems (light, temperature, and timer sensors), and regular maintenance of HVAC systems. With the implementation of technical, managerial, and operational efficiency strategies, it is estimated that energy consumption savings could reach 20–30%, or around 60,000 kWh per month, without compromising visitor comfort.